PROFIL HUTAN MANGROVE TAMAN NASIONAL BALURAN JAWA TIMUR (Mangrove Forest Profile of Baluran National Park East Java) - Sudarmadji Sudarmadji (The East Java Biological Society, 2003)
Five mangrove profiles at Baluran National Park East Java were studied. The location was Popongan, Batu Sampan, Kelor-Manting, Si Rondo Si Macan, dan Bilik beach. Each profile was found to be different in their distribution and population. They have demonstrated that there is no constant sequence for mangrove of contrasted areas, because some species tend to prefer a more seaward of a more landward site.